2018
DOI: 10.15252/embj.201798772
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrative and drug‐resistant slow‐cycling cells support metabolic heterogeneity in glioblastoma

Abstract: Metabolic reprogramming has been described in rapidly growing tumors, which are thought to mostly contain fast‐cycling cells (FCCs) that have impaired mitochondrial function and rely on aerobic glycolysis. Here, we characterize the metabolic landscape of glioblastoma (GBM) and explore metabolic specificities as targetable vulnerabilities. Our studies highlight the metabolic heterogeneity in GBM, in which FCCs harness aerobic glycolysis, and slow‐cycling cells (SCCs) preferentially utilize mitochondrial oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(234 citation statements)
references
References 91 publications
25
209
0
Order By: Relevance
“…The relevance of FGFR1 for GSCs is further supported by increased survival after loss of FGFR1, as well as increased tumorigenicity of FGFR1+ cells. We and others have shown that ZEB1 is a key regulator of stemness, invasion and chemoresistance in GBM (7,12,42), and consistently we find that ZEB1 mediates the stemness effects of FGF2/FGFR1 signaling. Singh and colleagues have recently demonstrated that ZEB1, SOX2 and OLIG2 form an autonomous transcriptional loop in GBM, and can regulate their expression reciprocally (26).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The relevance of FGFR1 for GSCs is further supported by increased survival after loss of FGFR1, as well as increased tumorigenicity of FGFR1+ cells. We and others have shown that ZEB1 is a key regulator of stemness, invasion and chemoresistance in GBM (7,12,42), and consistently we find that ZEB1 mediates the stemness effects of FGF2/FGFR1 signaling. Singh and colleagues have recently demonstrated that ZEB1, SOX2 and OLIG2 form an autonomous transcriptional loop in GBM, and can regulate their expression reciprocally (26).…”
Section: Discussionsupporting
confidence: 85%
“…Human glioblastoma (hGBM) cells were cultured as described previously (7,12). Briefly, for GSC sphere culture, 5x10 4 Cell lines from the HGCC repository (28) were cultured in Neurobasal medium (Thermo Fisher) supplemented with B27 (Thermo Fisher) and 20ng/ml EGF and FGF2.…”
Section: Primary Human Glioblastoma Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…PTN and its target PTPRZ1 also may help promote stemness, signaling, and proliferation of neural progenitors and glioma tumor cells (Fujikawa et al 2016;Zhang et al 2016;Fujikawa et al 2017). Moreover, FABP7 expression and activity have been associated with lipid metabolism in slow-cycling GBM tumor cells, proposed to be responsible for tumor recurrence (Hoang-Minh et al 2018).…”
Section: Discussionmentioning
confidence: 99%